PREMEDITATED MURDER ON SHIP WHEN SEEKING LIFE PRESERVES ACCORDING TO HUMAN RIGHTS PERSPECTIVE - Yustisio Mahendra; Tantimin Tantimin (Legal Spirit, 2022)
Sustaining life means a person is trying to save his life so that he can continue his daily life. Defense is not only in eating, drinking, exercising, maintaining a healthy body, and getting enough sleep but also in surviving in a state of urgency. Circumstances force a person to do anything in the hope of preserving their life. This study aims to find out in-depth the study of Force majeure, which has the meaning of a condition where a particular place can experience urges that cannot be prevented due to natural factors. Due to force majeure, such as goods, forced circumstances can still be forgiven due to natural factors. However, it is different from humans in terms of human rights if it is related to the Criminal Code (having a general character) and the Human Rights Law (having a unique character), following the Lex specialis derogat Legi generali principle. It is the rule of law that tends to be specific, which can contradict the general law. Premeditated murder is a crime against life regulated in Article 340 of the Indonesian Criminal Code. Premeditated murder is an act that stands alone with ordinary murder as regulated in Article 338 of the Indonesian Criminal Code. The provisions contained in the act of premeditated murder are a repetition of the act of murder in Article 338 of the Criminal Code. One more element is added, "with a prior plan." The approach used in reviewing this research is the approach through the law (statute approach) and conceptual approach. This research is legal (juridical normative) by understanding various sources. The primary is based on legislation, the secondary is based on book and journal studies, and the last is tertiary, based on dictionaries to find foreign languages that are difficult to understand.